‘Some Agreeable Conversation’: Jonathan Edwards Among Early American Baptists - Lumpkin Aaron L. (Perichoresis: The Theological Journal of Emanuel University, 2023)
Jonathan Edwards has long been recognized for his theology, philosophy, biblical studies, and pastoral ministry. The influence of Edwards’s life and ministry has stretched both far and wide. While his effect among English Baptists has been examined in a variety of ways, less attention has been given to his influence among early Baptists in North America. This article provides a survey of the research concerning Edwards’s influence upon early Baptists in North America. It argues that early Baptists in North America have been more influenced by Edwards than previously recognized. These Baptists looked to Edwards for instruction on Scripture, theology, piety, conversion and revival, preaching and pastoral ministry, and missions. Yet, more work needs to be done to understand the full scope of the reception of Edwards by early Baptists in North America.